The Practice, Challenge and Solution of English Teaching for Students with Reading Disability in An Inclusive Classroom - Ni Luh Eka Ciptarini Wijayanti; I G A Lokita Purnamika Utami; Luh Gd Rahayu Budiarta (STKIP AGAMA HINDU SINGARAJA, 2025)
This study investigates the implementation of English teaching for students with reading disabilities within an inclusive classroom at one school in East Bali. Employing a case study design, the research aims to explore the teaching procedures, challenges encountered by the teacher, and strategies employed to address these challenges when instructing students with reading disabilities. The subject of this study is an English teacher responsible for class 8A, which includes a student with a reading disability. As the sole participant, the teacher serves as both the population and the sample. Data were collected through classroom observations and in-depth interviews with the teacher, then analyzed using Miles and Huberman’s Interactive Model of Qualitative Data Analysis. The findings reveal that English teaching in the inclusive classroom follows three main stages: pre-activity, while-activity, and post-activity. Key challenges identified include managing students with reading disabilities, handling a large class size, and coping with limited resources. To overcome these challenges, the teacher employs various strategies such as the use of the bilingual method, reading aloud, and giving positive reinforcement. This study enhances theoretical understanding of English language teaching for students with reading disabilities in inclusive settings and offers practical insights for educators to effectively support diverse learners. The findings have important implications for improving instructional practices in inclusive education, particularly in resource-constrained contexts, and provide a foundation for teacher training programs aimed at fostering equitable language learning opportunities for all students.